Solving class of mixed nonlinear multi-term fractional Volterra-Fredholm integro-differential equations by new development of HAM - Zainidin Eshkuvatov; Zaid Laadjal; Shahrina Ismail (Vilnius Tech, 2026)
Indexed by WOS / SCOPUS / ERA